An unusual cutaneous manifestation of myelodysplastic syndrome: "pseudo-Koebner phenomenon". Issue 11 (November 1998) - DasGupta, R; Fairham, S A; Womack, C; Burton, C; Sivakumaran, M
Abstract : An unusual and hitherto unreported complication of myelodysplastic syndrome is reported: the "pseudo-Koebner phenomenon." The skin lesions were characterised by exuberant "fleshy" masses at the sites of intravenous cannulation and skin trauma, and by histological evidence of chronic inflammation with focal necrosis and abscess formation. No evidence of dermal infiltration by malignant haemopoietic cells was seen. The exact aetiopathology of the phenomenon is unclear but an inappropriate and exaggerated inflammatory response owing to aberrant mediator mechanisms that are known to occur in some cases of myelodysplastic syndrome may be implicated.